A preliminary study of Patient Lifting Robot for Nurse assistance - Muralindran, M.; Nagarajan, R.; Sazali, Yaacob; Mohd Yunus, Hamid; Renee, Chin (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 14th - 15th May 2005 at Putra Palace Hotel, Kangar, Perlis.